Investigating modern history - Dallimore, Jonathon; Kandalaft, Rima; Kelly, Brad; Tol, David Van (Cengage Learning, 2017)
Investigating Modern History is tailored specifically to the new Stage 6 Modern History syllabus for NSW Year 11 students. Taking an inquiry approach to all nature and methods of Modern History options and popular case studies, this student resource covers the key content, skills and assessment practices of Modern History at Year 11. Investigating Modern History also provides students with practical strategies and advice for approaching the Historical Investigation.